EPR IN MODERN COORDINATION CHEMISTRY. SPIN-SPIN INTERACTIONS WITHIN CU(II) PAIRS OF POLYNUCLEAR COMPLEXES (Вісник Київського національного університету імені Тараса Шевченка. Хімія, 2007)
The peculiarities of the exchange interactions between copper(ll) atoms are considered for the case of poly- and heteropolynuclear complexes. EPR-spectroscopy has been shown to have advantages for the investigation of weak spin-spin interactions.